PENDAMPINGAN DESA WISATA DALAM MENGEMBANGKAN POTENSI DESA MELALUI PROMOSI DIGITAL DI DESA TANGKUP KECAMATAN SIDEMEN, KARANGASEM BALI - Komang Krishna Yogantara; Putu Agus Prayogi; Sulistyoadi Joko Saharjo; Made Hedy Wartana (Synergy and Society Service, 2022)
Tangkup Village is a village located in the Sidemen District, Karangasem Regency which is the name of an ancient village in Bali, has high potential in the agricultural, plantation and tourism sectors. After the Covid-19 pandemic, which made all tourism activities in Tangkup Village need to be revived, there were several obstacles that had to be overcome, such as the inconsistency of tourism activists in promoting tourist destinations in Tangkup Village, especially in the use of digital promotions. The purpose of this service is to provide assistance to activists and in an effort to improve digital marketing strategies in Tangkup Village. The method used in this service is training and mentoring. Based on the results of the training and assistance carried out, it shows that there is an improvement, able to develop village potential, understanding of digital media management as a means of digital marketing media which includes content creation and suitability, completeness of information in promotional videos, efforts to increase insight with paid advertising and others. etc.